An Import, Export and Transshipment Model for Air Cargo Operations - Stausberg, Lisa (2012)
This dissertation has been prepared in order to develop an import, export and transshipment flow model for air cargo operations and thereby answer the research question: “How do import, export and transshipment processes work in the airfreight environment?” This project has been introduced and supported by British Airways World Cargo in order to reach a better understanding and visualisation of their internal processes.